2015
DOI: 10.1124/dmd.115.065136
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxide–Mediated Oxidative Rearrangement of the Pyrazinone Carboxamide Core of Neutrophil Elastase Inhibitor AZD9819 in Blood Plasma Samples

Abstract: This study focused on the mechanistic interpretation of ex vivo oxidation of a candidate drug in blood plasma samples. An unexpected lipid peroxide-mediated epoxidation followed by a dramatic rearrangement led to production of a five-membered oxazole derivative from the original six-membered pyrazinone-carboxamide core of a human neutrophil elastase inhibitor, 6-(1-(4-cyanophenyl)-oxazole-4-carboxamide was characterized by accurate-mass tandem mass spectrometry fragmentations, by two-dimensional NMR and X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In a previous experience, generating putative structures with envisaged rearrangement mechanisms was an effective way of assisting structural identification on a dramatically rearranged oxidation product in plasma for a candidate drug acting as a human neutrophil elastase inhibitor (Gu et al, 2015). Two intuitive thoughts have guided the proposal for possible mechanisms in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous experience, generating putative structures with envisaged rearrangement mechanisms was an effective way of assisting structural identification on a dramatically rearranged oxidation product in plasma for a candidate drug acting as a human neutrophil elastase inhibitor (Gu et al, 2015). Two intuitive thoughts have guided the proposal for possible mechanisms in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the synthetic complexity of the proposed structures or because the proposed structures are simply unable to be provided. When 1 H NMR information is very limited at core structures before and after biotransformation/rearrangement, 2D NMR data and educated guesses on possible formation mechanisms to draft putative structures for verification can constitute an effective approach to eventually confirm metabolite structure. , As illustrated previously, the biosynthesis and NMR characterizations and chemical synthesis of the proposed AZD7325 M9 metabolite standard, pimasertib M554 standard, and navoximod 306-P1 metabolite standard were essential for definitive metabolite structure elucidation.…”
Section: Approaches In Tracking Missing Metabolitesmentioning
confidence: 99%
“…It has been previously reported that comparing observed carbon chemical shifts with predicted carbon chemical shifts of putative structures can be an effective approach for structural elucidation when 1 H NMR information is limited at the chemical structure of biotransformation (Gu et al, 2015).…”
Section: In Vitro Metabolism Of [Nitrile-14 C]biib104 In Rlm Dlm and Hlmmentioning
confidence: 99%